KREATIVITAS SANDI SUNAN KENDANG DALAM PERTUNJUKAN DANGDUT KOPLO DI BANYUWANGI - Buwono, Gigih Among; Purnomo, Wahyu (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Creativity of Sandi Sunan Kendang in Dangdut Koplo Performances in Banyuwangi discusses the phenomenon of a drum musician whose real name is Sandi Pratama who is usually called Sandi Sunan Kendang. He is one of the drum musicians who popularized the Banyuwangian style of dangdut koplo music in East Java. In essence, this article discusses Sandi Sunan Kendang's activities related to his life background in the development of Dangdut Koplo with Banyuwangi nuances. Sandi Sunan Kendang comes from a family of artists, he departed from a traditional artist to enter the world of dangdut koplo. As a special dangdut koplo musician as a drum player, he includes Banyuwangian drum patterns such as Kuntulan with the aim that drum musicians and young people can learn about regional culture, especially Banyuwangi. Keywords: Sandi Sunan Kendang, dangdut koplo, creativity